Development of Number Slides for the Counting Ability of Group B Children at RA Jami’ul Muhimmah Pelambik - Fitri, Dia’ul; Yuliastri, Nur Adiyah; Nuria, Ratri (SALIHA: Jurnal Pendidikan Islam, 2025)
This Research aims to develop and see the effectiveness of number slide media on the numeracy skills of group B Children. The development model used is the Borg and Gall type which has been simplified into 6 stages, including data collection, planning, initial product development, initial field trials, revision results of initial field trials, and field trials. The learning media developed is validated by media experts and material experts. The initial field trial subjects were 5 children and in the field trial there were 15 group B Kindergarten children. The instrument used was an Observation sheet, The data analysis technique used is the T test. The results of this study show that the validation results from media experts obtained a score of ‘’33’’ with a score range of 27.42 < Score range 17.02 < according to expectations’’ (BSH). There is a significant difference in the t-test regarding the development of number slide media on children’s numeracy skills, namely (t count = 7.024 > t table = 2.145). x² count < x² table (-156.21 < 23.685) the pre-test data is said to be normally distributed, in the post-test x2 count < x2 table (-635.60 < 23.685) is normally distributed suitable for use for the numeracy skills of children aged 5-6 years.